In vivo assessment of acute toxicity of juvenile red hybrid tilapia (Oreochromis sp.) exposed to roundup® (glyphosate-based) herbicide - Hidayatul Nabilah Mat Yasin. (2018)
Malaysia depends heavily on the agriculture and many herbicides are commonly used to kill weeds in vegetable farms and orchards. Glyphosphate-based herbicide is one of the most used herbicide in Malaysia. Herbicides that are used near pond water or water source can affect the water quality and environment. In this experiment, 25 juvenile Red hybrid Tilapia were exposed to different concentrations of Roundup® (14mg/L, 16mg/L, 18mg/L and 20mg/L) for 24 hours with control group. During the experiments, any changes in behaviors were recorded and the fish were sacrificed by severing the spinal cord where the gills and brain were collected. The behaviour changes to time and concentration of herbicide were irregular. For the behaviors, we can observe the fish was gasping, loss of balance, dull and eventually settled at the bottom and eventually die. In order to study the effect of Roundup®, glyphosate-based herbicide, histopathological changes of gills and brain were observed under light microscope. Gills histology revealed epithelial oedema, epithelial lifting of secondary lamellae, thickening (hyperplasia) of primary lamellae, fusion of secondary lamellae, congestion in primary and secondary lamellae blood vessels. Brain histology revealed congestion of cerebral blood vessels, slight congestion in granular and molecular layers of cerebrum, demyelination of neuron cells, infiltration of inflammatory cells and vacuolative degeneration in the molecular layer. The lethal dose at 50% mortality (LD₅₀) of Roundup® herbicide was determined by using Karber methods which show that 14mg/L is the lethal dose.